Knowledge, Information and Creativity Support Systems Selected Papers from KICSS'2014 - 9th International Conference, held in Limassol, Cyprus, on November 6-8, 2014 - Kunifuji, Susumu; Papadopoulos, George Angelos; Skulimowski, Andrzej M.J.; Kacprzyk , Janusz; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This volume consists of a number of selected papers that were presented at the 9th International Conference on Knowledge, Information and Creativity Support Systems (KICSS 2014) in Limassol, Cyprus, after they were substantially revised and extended. The 27 regular papers and 19 short papers included in this proceedings cover all aspects of knowledge management, knowledge engineering, intelligent information systems, and creativity in an information technology context, including computational creativity and its cognitive and collaborative aspects. .
Message from the Conference Chairs -- The Algorithm of Discovery: Making Discoveries on Demand -- The Art of Anticipatory Decision Making -- On Modeling Human-Computer Co-Creativity -- Comparison of the Two Companies' Staff by the Group Idea-Marathon Training on Creativity and Motivation -- Using Appropriate Context Models for CARS Context Modelling -- Computational Creativity for Intelligence Analysis -- Bus Scheduling in Dynamical Urban Transport Networks with the Use of Genetic Algorithms and High Performance Computing Technologies -- MCDA and LCSA - A Note on the Aggregation of Preferences -- A Model for Managing Organizational Knowledge in the Context of the Shared Services Supported by the E-Learning -- Online Communities of Practice: Social or Cognitive Arenas? -- Knowledge Extraction and Annotation Tools to Support Creativity at the Initial Stage of Product Design: Requirements and Assessment -- Web Board Question Answering System on Problem-Solving Through Problem Clusters -- A PHR Front-End System with the Facility of Data Migration from Printed Forms -- Investigating Unit Weighting and Unit Selection Factors in Thai Multi-Document Summarization -- On the Use of Character Affinities for Story Plot Generation -- Vicarious: A flexible framework for the creative use of sensed biodata.-Application of Rough Sets in k Nearest Neighbours Algorithm for Classification of Incomplete Samples -- An Application of Firefly Algorithm to Position Traffic in NoSQL Database Systems -- Length of Hospital Stay and Quality of Care -- Bio-Inspired Hybrid Intelligent Method for Detecting Android Malware -- Predicting the Impact of Advertisements on Web Pages Aesthetic Impressions -- OntOSN - An Integrated Ontology for the Business-Driven Analysis of Online Social Networks -- Social Media and Communication Processes at Work: Evidence from China -- Educators as Game Developers - Model-Driven Visual Programming of Serious Games -- First Year Students' Algorithmic Skills in Tertiary Computer Science Education -- Implementing a Social Networking Educational System for Teachers' Training -- Virtual Environment for Creative and Collaborative Learning -- A Semiotic and Cognitive Approach to the Semantic Indexation of Digital Learning Resources -- The Significance of 'Ba' for the Successful Formation of Autonomous Personal Knowledge Management Systems -- The Significance of Memes for the Successful Formation of Autonomous Personal Knowledge Management Systems -- Computer Creativity in Games - How Much Knowledge is Needed? -- When Engineering and Design Students Collaborate:The Case of Website Development Workshop -- Knowledge-Managing Organizational Change Effectors, Affectors and Modulators in an Oil and Gas Sector Environment -- From Computational Creativity Metrics to the Principal Components of Human Creativity -- ASocial Creativity Support Tool Enhanced by Recommendation Algorithms: The Case of Software Architecture Design -- The Approach to the Extension of the CLAVIRE Cloud Platform for Researchers' Collaboration -- iDAF-drum: Supporting Practice of Drumstick Control by Exploiting Insignificantly Delayed Auditory Feedback -- Novel Methods for Analyzing Random Effects on ANOVA and Regression Techniques -- nVidia CUDA Platform in Graph Visualization -- A Method for Opinion Mining of Coffee Service Quality and Customer Value by Mining Twitter -- Using Wiki as a Collaboration Platform for Software Requirements and Design -- Enhancing Software Architecture via a Knowledge Management and Collaboration Tool -- Collaborative Requirement Prioritization for an E-Recruitment Platform for Qualifies but Disadvantaged Individuals -- Text Comparison Visualization from Two Information Sources by Network Merging and Integration -- Collective Knowledge and Creativity: The Future of Citizen Science in the Humanities -- Aligning Performance Assessments with Standards: A Practical Framework for Improving Student Achievement in Vocational Education.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence